PENGARUH KUALITAS LAYANAN, KEPERCAYAAN, DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN (STUDI EMPIRIS PADA PELANGGAN LEGEND COFFEE SEMARANG) - Anisa Ulfah Nugraheni, 12.05.51.0055; Widyasari, Suzy (Students Journal of Economic and Management, 2016)
This study heads for analyzing the effect of service quality, trust, and satisfaction to the customer loyalty in the Legend Coffee Semarang. The sample in the research is the customers of Legend Coffee Semarang as much as 100 peoples. This study used purposive sampling technique. The sample criteria that had been used were the customer of Legend Coffee Semarang which were 17 years old minimum, and has been done purchasing for 3 times in the last three months. Methods of data collection in this study is questionnaires filled out by therespondents are consumers of Legend Coffee Semarang. The analysis used in this research include factor analysis to examine the validity, the cronbach alpha formula to examine the reliability of the instrument, regression analysis to examine how big are the influences, the regression analysis to examine how big is the effect partially of each independent variable tested using the determination coefficient and model fit test to test and to prove the partially effect of each independent variable. The result of analysis can be concluded that: the service quality could give the positive and significant impact to the customer loyalty of Legend Coffee Semarang, the trust could give the positive and significant impact to the customer loyalty of Legend Coffee Semarang and satisfaction could give the positive and significant impact to the customer loyalty of Legend Coffee Semarang. Keywords: service quality, trust, satisfaction and customer loyalty